An animal model of genetic predisposition to develop acquired epileptogenesis: The FAST and SLOW rats. (29th August 2019) - Leung, Wai Lam; Casillas‐Espinosa, Pablo; Sharma, Pragati; Perucca, Piero; Powell, Kim; O'Brien, Terence J.; Semple, Bridgette D.
Abstract: Epidemiological data and gene association studies suggest a genetic predisposition to developing epilepsy after an acquired brain insult, such as traumatic brain injury. An improved understanding of genetic determinants of vulnerability is imperative for early disease diagnosis and prognosis prediction, with flow‐on benefits for the development of targeted antiepileptogenic treatments as well as optimal clinical trial design. In the laboratory, one approach to investigate why some individuals are more vulnerable to acquired epilepsy than others is to examine unique rodent models exhibiting either vulnerability or resistance to epileptogenesis. This review focuses on the most well‐characterized of these models, the FAST (seizure‐prone) and SLOW (seizure‐resistant) rat strains, which were derived by selective breeding for differential amygdala electrical kindling rates. We describe how these strains differ in their seizure profiles, neuroanatomy, and neurobehavioral phenotypes, both at baseline and after a brain insult, with this knowledge proving fruitful to identify common pathological abnormalities associated with seizure susceptibility and psychiatric comorbidities. It is important to note that accruing data on strain differences in multiple biological processes provides insight into why some individuals may be more vulnerable to epileptogenesis, although future studies are evidently needed to identify the precise molecular and genetic risk factors. Together, the FAST and SLOW rat strains, and other similar experimental models, are invaluable neurobiological tools to investigate the effect of genetic background on acquired epilepsy risk, as well as the poorly understood relationship between epilepsy development and associated comorbidities.